1999
DOI: 10.1111/j.1528-1157.1999.tb00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Temporal Lobe Epilepsy Before Epilepsy Surgery

Abstract: Summary:Purpose: This study examined the association of depression with laterality of epilepsy surgery in patients with temporal lobe epilepsy before standard lobectomy.Methods: Forty-nine patients presented for EEG telemetry for localization of epilepsy and eventual temporal lobectomy. Patients underwent routine neuropsychiatric evaluation blinded for epileptic focus, including ratings on depression. Patients were grouped according to right (n = 25, M = 1O/F = 15) and left (n = 24, M = 13/F = 11) temporal lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 51 publications
1
20
0
1
Order By: Relevance
“…Other studies, however, found that the interictal, presurgical rate of depression is higher in right-sided temporal lobe epilepsy (9,10).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Other studies, however, found that the interictal, presurgical rate of depression is higher in right-sided temporal lobe epilepsy (9,10).…”
Section: Discussionmentioning
confidence: 83%
“…The side of epilepsy surgery may affect subsequent psychiatric morbidity, with depression having a greater prevalence after right-sided surgery (3,(9)(10)(11).…”
mentioning
confidence: 99%
“…Some studies indicated a higher rate of interictal depression in epileptic patients with left-sided foci [25,26,27]; conversely other studies identified a higher rate of interictal depression in right-sided TLE [28, 29] or no relationship at all [24]. In our study, although no particular side or focus predominance was found in the group of epileptic patients with depression as a whole, moderate to severe depression tended to be more often associated with a temporal or frontal right-sided focus, but this association did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…More complex analyses suggest patients with left temporal lobe epilepsy, along with other factors such as being female (68) or concurrent frontal lobe dysfunction (67,69), are predisposed to depressive symptoms. To complicate matters, a recent report (70) found that depression was more prominent in patients with right temporal lobe epilepsy. The lack of clarity on the issue of depression and laterality merits further study.…”
Section: Discussionmentioning
confidence: 99%